2013
DOI: 10.5625/lar.2013.29.2.77
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative and qualitative analysis of rat pup ultrasonic vocalization sounds induced by a hypothermic stimulus

Abstract: Ultrasonic vocalizations (USVs) are essential communicative sounds used between rodent pups and their mother. Rat pups emit USVs in stressful situations, such as when they are cold or separated from the nest. We verified the ontogenetic changes in USVs emitted by infant rats isolated from their mother during the pre-weaning period. The number of calls, and the median frequency and first peak of frequency of the calls were measured at 1, 3, 5, 7, 10, 12, and 14 days postnatal age in Wistar-Imamichi rats. Pups w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 14 publications
5
20
0
Order By: Relevance
“…The pitch of USVs from control pups decreased with age, as previously reported (Kromkhun et al, 2013), but increased with age in PS pups, further suggesting atypical development following PS. Isolation-induced USVs are inherently social (Hofer et al, 2002;Harmon et al, 2008), and reductions of USVs have been found in rodent models of ASDs (Crawley, 2007;Higashida et al, 2011).…”
Section: Discussionsupporting
confidence: 82%
“…The pitch of USVs from control pups decreased with age, as previously reported (Kromkhun et al, 2013), but increased with age in PS pups, further suggesting atypical development following PS. Isolation-induced USVs are inherently social (Hofer et al, 2002;Harmon et al, 2008), and reductions of USVs have been found in rodent models of ASDs (Crawley, 2007;Higashida et al, 2011).…”
Section: Discussionsupporting
confidence: 82%
“…As previously observed, we confirmed that the USVs produced by WT pups in response to a cool challenge changed as the pups matured (Kromkhun et al, 2013). Responses of WT pups to cool exposure significantly decrease as their fur growth and their ear canals open at 1 week of age.…”
Section: Resultssupporting
confidence: 90%
“…Previous studies have elucidated the developmental changes in the acoustic characteristics of USV emitted by rat pups upon maternal isolation (Kehoe & Harris, 1989;Elsner et al, 1990;Brudzynski et al, 1999;Schwarting & Wohr, 2012;Kromkhun et al, 2013;Wada, 2017) and reported that the number of USVs increases on PNDs 3-5 to reach a…”
Section: Discussionmentioning
confidence: 99%
“…High-ethanol male Low-ethanol male Control male High-ethanol female Low-ethanol female Control female peak on PNDs 5-11 (Brudzynski et al, 1999;Schwarting & Wohr, 2012). USV duration exhibits an age-dependent increase, whereas USV frequency exhibits an age-dependent decrease (Elsner et al, 1990;Kromkhun et al, 2013). Subsequently, as they age, the pups become less dependent on their dam because they are covered with body hair and can regulate their body temperature.…”
Section: Rms Of Usv Amplitude (V)mentioning
confidence: 99%